Progressive reductions in blood glutamine levels and improved performance occur with competitive swim training - Koziris, L. P.; Hickson, R. C.; Chatterton Jr, R. T.; Groseth, R. T.; Christie, J. M.; Osborne, D. F.; Karl, I. E. (Medicine & Science in Sports & Exercise, 1999)
Whether blood glutamine levels are altered in response to varied training volumes and their relationships to performance were evaluated in collegiate swimmers. One male and one female team were studied at the start, after two and four months (2-4 months had the highest training volume), after five months near the end of tapering (male team only), and several days after training and competitions ended. The male team displayed a 17% reduction in blood glutamine after two months and a further diminution to 28% by the end of training. However, the female team displayed a reduction of 14% only after four months of training, which, along with all other measures, was not significantly different to the initial value. Both teams exhibited steady performance improvements (M = 6.4%; F = 4.7%) throughout the whole season. Blood glutamate concentrations increased linearly throughout the season for both teams (M = 74%; F = 63%). Performances improved as glutamine levels declined. Thus, glutamine measures are not a potential marker for overtraining. Implication: Glutamine is not associated with overtraining in swimmers.